EFFICACY OF CLASSICAL CAROTID ENDARTERECTOMY USING TEMPORARY SHUNT - I. V. Mikhailov; A. V. Gusinskiy; V. V. Shlomin; O. V. Orlova; T. B. Rakhmatillaev; P. D. Mohan (Вестник хирургии имени И.И. Грекова)
The study generalized the 15-year experience of classical carotid endarterectomy performance with application of a temporary carotid shunt and an autovenous path in 325 patients. There were analyzed the more frequent complications in standard groups. Advantages of given method were determined and it was specified the ways, which facilitated to reduction of intraoperative risks and increase of technical quality realization of different stages of surgery.